Polycation-functionalized gold nanoparticles with different morphologies for superior gene transfection. Issue 12 (28th March 2015) - Yan, Peng; Wang, Ranran; Zhao, Nana; Zhao, Hong; Chen, Da-Fu; Xu, Fu-Jian
<x xml:space="preserve">Abstract</x> PDMAEMA-functionalized Au nanoparticles with different morphologies are designed to investigate the effects of their size and shape on gene transfection.